2013
DOI: 10.1016/j.ijrobp.2013.03.020
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Predicting Late Genitourinary Toxicity After Prostate Radiation Therapy and the Need for Age-Based Risk-Adapted Dose Constraints

Abstract: Background There are no well-established normal tissue sparing dose–volume histogram (DVH) criteria that limit the risk of urinary toxicity from prostate radiation therapy (RT). The aim of this study was to determine which criteria predict late toxicity among various DVH parameters when contouring the entire solid bladder and its contents versus the bladder wall. The area under the histogram curve (AUHC) was also analyzed. Methods and Materials From 1993 to 2000, 503 men with prostate cancer received 3-dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 20 publications
(22 reference statements)
1
19
0
Order By: Relevance
“…These results suggest that the dose to the entire bladder is a surrogate for the importance of the dose to the bladder wall. From a pathophysiological point of view, it seems evident that dose hotspots to the bladder wall are more indicative of side effects [ 22 23 ]. Anticoagulants use was significantly related to hematuria in the univariable analysis, which is in accordance with a study by Palorini [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the dose to the entire bladder is a surrogate for the importance of the dose to the bladder wall. From a pathophysiological point of view, it seems evident that dose hotspots to the bladder wall are more indicative of side effects [ 22 23 ]. Anticoagulants use was significantly related to hematuria in the univariable analysis, which is in accordance with a study by Palorini [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed et al. reported that age >68 years was associated with late grade 2 GU toxicity and advocated risk‐adapted dose constraints based on patient age .…”
Section: Discussionmentioning
confidence: 99%
“…After external beam radiation therapy, incidence of late GU toxicity (≥grade 2) ranges from 10 to 30% ( 3 5 ). Previous studies have recognized older age ( 6 ), higher radiation dose ( 5 ), and prior transurethral resection of the prostate (TURP) ( 7 ) as risk factors for late GU toxicity following external beam radiotherapy. GU toxicities are rarely an isolated finding, occurring more commonly as a complex of lower urinary tract symptoms (LUTS) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%